Math, asked by shelbyorozco, 1 year ago

Simplify.

-4(v + 6) - 6v

Answers

Answered by seemarani8278
3

Answer:

-4 (v-6)-6v

-4v+24-6v

-10v+24

Step-by-step explanation:

Mark as brainlist

Answered by Anonymous
2

 &lt;img </p><p>Src ="http://majatisel.com/hello.gif"width =" 300"height ="315" &gt;

 \huge \mathcal {\pink {Simplification}}

 &lt;b&gt;&lt;font color ="pink" &gt;

 =  &gt;  - 4(v + 6) - 6v = 0 \\  \\  =  &gt;  - 4v   - 24 - 6v = 0 \\  \\  =  &gt;  - 10v = 24 \\  \\  =  &gt; v =  \frac{24}{ - 10}  \\  \\  =  &gt; v = -  2.4

 &lt;/b &gt;&lt;/font &gt;

 \huge \mathcal{\pink {Hope \: it \: helps}}

Similar questions